The usborne internet-linked children's encyclopedia - Brooks, Felicity; Hancock, David (Usborne London, 2012)
A must-have encyclopedia with over 1,500 amazing photographs, illustrations and diagrams. Packed full of knowledge just waiting to be absorbed by fact-hungry children, including information about our world, animals and plants, how the human body works, history, science, technology and space - plus a complete set of maps of the world.